Dinâmica do uso da terra e naturalidade do entorno da Floresta Nacional de Irati - Almeida, Dayana (2017)
Protected areas are an important strategy for the maintenance of biodiversity. However, land use dynamics of the protected areas buffer zones receive little attention in literature. The goal of this research was to identify the landscape constraints and modelers in order to maintain the naturalness of the scenarios surrounding Irati National Forest, based on the temporal and spatial dynamics of the land use and cover analysis and the Distance to Nature Index (D2N) application for the period from 1986 to 2016. The land use and cover dynamics for the study area was obtained by on-screen digitizing of LandSat-5 and LandSat-8 imagery for 1986, 1997, 2011, and 2016 in ArcGis 10.2 software, using the hemeroby scale. A trajectorie analises between the years 1986-1997, 1997-2011, 2011-2016, 1986-2016, and 1986-2016 were used to evaluate the landscape dynamics. The D2N index was applied to measure the anthropogenic impact on biodiversity based on the dynamics of land use and cover of the study area for the four years. To test the null hypothesis of the D2N index between 1986, 1997, 2011, and 2016, a multivariate permutation analysis with Euclidean distance was performed. There was an increase of the anthropisation in the surrounding Irati National Forest. However, the region still presents an expressive degree of naturalness, mainly when compared to others surrounding protected areas. The changes in the landscape presented a different dynamic regarding the different agricultural production systems in the study area. In this way, as the maintenance practices of Irati National Forest natural condition and its surroundings will also present different profiles of each production system. The statistical analysis of the D2N results shows that only 1997 presented a statistically significant difference. The results demonstrate that D2N can be an effective tool for monitoring and planning to identify a natural condition and areas with greater anthropogenic influence, proposing scenarios for biodiversity conservation.